2021
DOI: 10.1186/s12889-021-11202-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s experiences of social distancing behavioural guidelines during the Covid-19 pandemic ‘lockdown’ in the UK, a qualitative interview study

Abstract: Background Covid-19 triggered the rapid roll-out of mass social distancing behavioural measures for infection control. Pregnant women were categorised as ‘at risk’ requiring extra vigilance with behavioural guidelines. Their understanding and ability to adhere to recommendations was unknown. Objectives To complete a behavioural analysis of the determinants of recommended social distancing behaviour in pregnant women, according to the ‘capability, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 18 publications
0
58
1
2
Order By: Relevance
“…Participants echoed the voices of pregnant women that during the pandemic, they needed more time and support from their midwives. 31 This was difficult due to staffing pressures, already present prior to the pandemic, 5 which worsened due to additional tasks and a reduced workforce. 1 Although the literature shows that most frontline staff prioritised service users’ needs above their own health anxiety during the pandemic, 7 an over-worked and distressed workforce is less able to provide high-quality healthcare, creating a downwards spiral.…”
Section: Discussionmentioning
confidence: 99%
“…Participants echoed the voices of pregnant women that during the pandemic, they needed more time and support from their midwives. 31 This was difficult due to staffing pressures, already present prior to the pandemic, 5 which worsened due to additional tasks and a reduced workforce. 1 Although the literature shows that most frontline staff prioritised service users’ needs above their own health anxiety during the pandemic, 7 an over-worked and distressed workforce is less able to provide high-quality healthcare, creating a downwards spiral.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, pregnant women had been demonstrated to meet their social support needs mostly through virtual means, with only approximately one in five meeting with someone in-person [ 25 , 26 ]. Our understanding of how digital communication technology to attenuate people’s sense of isolation and loneliness remains, however, limited [ 27 ]. Our study revealed more contacts in non-essential social settings among pregnant women, suggesting a minimal level of social contacts that women reporting as being pregnant may consider as vital.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal stress may pave the way to postnatal symptoms of depression and anxiety for the mother, and worse behavioural, emotional, cognitive, and physical outcomes for the children 18 . Social and physical distancing likely threaten to aggravate the feelings of concern and isolation that will produce these negative health consequences 19 . In this study, pregnant women maintained a similar level of contacts in “non-essential” social settings – such as other people’s home, a place of entertainment or sports – regardless of NPIs, suggesting a minimum level of social contacts that they may consider as vital.…”
Section: Discussionmentioning
confidence: 99%
“…CoMix is an online longitudinal, multi-country social contact survey that follows individuals in 19 European countries over the course of the COVID-19 pandemic. The survey asks people aged 18 or above about their awareness, perceptions, social contacts, and health condition over the course of the COVID-19 pandemic.…”
Section: Study Design and Settingmentioning
confidence: 99%